Market power in maritime transport of Brazilian imports - Strasburg, Jessica (2018)
Market power is present in shipping industry as carriers are able to charge freights above their marginal costs due to presence of markup related variables – import elasticities, low competition among trade routes and import tariffs. The present work presents OLS and fixed effects estimations for the impact of each markup related variables for freights in Brazil, as well as some insight about the sources of market power across economic sectors and trade partners. Tariffs seem to play the most important role in enabling higher freights, although all other variables are shown to also matter. Import elasticities have a negative impact on market power, and their coefficients are very significant for industrial goods. The number of carriers competing on a route also tends to diminish freights. Despite showing positive elasticity to freights in all sectors, distances are only definite for import freights of agricultural products.